Temperature dependence of ion track formation in quartz and apatite. (25th October 2013) - Schauries, D.; Lang, M.; Pakarinen, O. H.; Botis, S.; Afra, B.; Rodriguez, M. D.; Djurabekova, F.; Nordlund, K.; Severin, D.; Bender, M.; Li, W. X.; Trautmann, C.; et al.
<x xml:space="preserve">Abstract</x> Ion tracks were created in natural quartz and fluorapatite from Durango, Mexico, by irradiation with 2.2 GeV Au ions at elevated temperatures of up to 913 K. The track radii were analysed using small‐angle X‐ray scattering, revealing an increase in the ion track radius of approximately 0.1 nm per 100 K increase in irradiation temperature. Molecular dynamics simulations and thermal spike calculations are in good agreement with these values and indicate that the increase in track radii at elevated irradiation temperatures is due to a lower energy required to reach melting of the material. The post‐irradiation annealing behaviour studied for apatite remained unchanged.